Culture, institutions and school achievement in Brazil - Lopes, Daniel Alisson Feitosa (2017)
This paper estimates the impact of culture on the academic performance of Brazilian students in standardized tests. Based on data with student identification, we apply an algorithm of surname classification that assigns the student, based on the surnames of his/her parents, to one of the following ancestry groups: Iberian, Japanese, Italian, Germanic, Eastern European and Syrian-Lebanese. We show that students with non-Iberian European or Japanese ancestry obtain statistically and substantively higher scores on 3rd and 5th grade standard Math tests, even with a large set of individual, family and municipal controls. We also tested the hypothesis of persistence of local institutions, established during the era of mass immigration to Brazil in the 19th and 20th centuries, and we showed that the mechanisms of family transmission of culture remain robust for students with Japanese and Italian ancestry.